Guillain–Barre Syndrome following lower segment caesarean section under spinal anesthesia: A case report - Prajjwol Luitel; Devansh Upadhyay; Nischal Neupane; Sujan Paudel; Prashant Gyawali; Bikram Prasad Gajurel; Ragesh Karn; Reema Rajbhandari; Niraj Gautam; Ashish Shrestha; Rajeev Ojha (Clinical Case Reports, 2022)
Abstract Symptoms of Guillain–Barre Syndrome (GBS) may be mistaken for typical puerperal changes, delaying diagnosis. Surgery and anesthesia may be triggers for GBS with an overall increase in pro‐inflammatory cytokines in the postpartum period. We report a unique case of GBS in the postpartum period who made a good recovery with supportive measures.